Characteristics of Computational Thinking in Solving Mathematical Problems based on Kolb's Learning Style - Miswanto, Miswanto (JMEA : Journal of Mathematics Education and Application, 2024)
The approach in this research is qualitative research with an exploratory descriptive research type. The subjects in this research were several students from the Mathematics Tadris study program, Faculty of Tarbiyah and Teacher Training, UIN Sayyid Ali Rahmatullah Tulungagung semester 5 who met the subject selection requirements. This research uses two types of instruments, namely researchers as the main instrument and supporting instruments which include questionnaires and tests. Based on the results of research and discussion about students' computational thinking processes in solving mathematical problems based on learning styles, namely (1) students' computational thinking processes in solving mathematical problems based on divergent learning styles start from the decomposition stage, algorithmic stage, decomposition stage, generalization stage, debugging stage, abstraction stage, and decomposition stage. Where the stages of computational thinking include incoherent, complete and systematic; (2) Students' computational thinking processes in solving mathematical problems based on the assimilation learning style start from the decomposition stage, abstraction stage, algorithmic stage, debugging stage, generalization stage, abstraction stage, and decomposition stage. Where the stages of computational thinking include incoherent, complete and unsystematic; (3) Students' computational thinking processes in solving mathematical problems based on the convergent learning style start from the decomposition stage, abstraction stage, algorithmic stage, debugging stage, generalization stage, algorithmic stage, abstraction stage, and decomposition stage. Where the stages of computational thinking include coherent, complete and systematic; and (4) Students' computational thinking processes in solving mathematical problems based on accommodation learning styles start from the decomposition stage, abstraction stage, generalization stage, algorithmic stage, and debugging stage. Where the stages of computational thinking are coherent, complete and systematic.